Phase II trial of upfront bevacizumab and temozolomide for unresectable or multifocal glioblastoma - Emil Lou; Katherine B. Peters; Ashley L. Sumrall; Annick Desjardins; David A. Reardon; Eric S. Lipp; James E. Herndon II; April Coan; Leighann Bailey; Scott Turner; Henry S. Friedman; James J. Vredenburgh (Cancer Medicine, 2013)
Abstract Patients with unresectable glioblastomas have a poor prognosis, with median survival of 6–10 months. We conducted a phase II trial of upfront 5‐day temozolomide (TMZ) and bevacizumab (BV) in patients with newly diagnosed unresectable or multifocal glioblastoma. Patients received up to four cycles of TMZ at 200 mg/m2 on days 1–5, and BV at 10 mg/kg on days 1 and 15 of a 28‐day cycle. Brain magnetic resonance imaging (MRI) was performed monthly. Therapy was continued as long as there was no tumor progression, grade 4 nonhematologic toxicity, or recurrent grade 4 hematologic toxicity after dose reduction. The primary end point was best tumor response as measured on MRI. Forty‐one patients were accrued over 12 months; 39 had a full set of MRI scans available for evaluation. Assessment for best radiographic responses was as follows: partial responses in 24.4%, stable disease in 68.3%, and progressive disease in 2.4%. Treatment‐related toxicities included seven grade 4 toxicities and one grade 5 toxicity (myocardial infarction). From this study, it was concluded that an upfront regimen of TMZ and BV for unresectable glioblastoma was well tolerated and provided a significant level of disease stabilization. Therapeutic toxicities were consistent with those seen in the adjuvant setting using these agents. The upfront approach to treatment of glioblastoma in the unresectable population warrants further investigation in randomized controlled phase III trials.